199 Red Cell Rejuvenation Targets Inflammatory Microparticles, free Haemoglobin and Redox Active Iron: Key Mediators of Transfusion Related Acute Lung Injury in Cardiac Surgery. (6th June 2015) - Qureshi, Saqib; Patel, Nishith; Wozniak, Marcin; Cardigan, Rebecca; Murphy, Gavin
Abstract : Background: Using porcine model of TRALI, we have previously demonstrated that red cell washing prior to transfusion fails to protect against organ injury after cardiac surgery. Red cell rejuvenation however, eliminated all metabolic, biochemical and histological features of TRALI. In current study we investigate the mechanisms that drive endothelial dysfunction and organ injury in response to stored RBC transfusion. Method: Recipient swine of allogenic blood were randomised as: Sham (n = 6), transfusion of: 1-day old RBC (n = 8), 14-day old RBC (n = 6), 14-day old RBC washed (n = 8) and rejuvenated-washed 14-day stored RBC (n = 8). Microparticles (MP), free haemoglobin and iron levels were measured in plasma and serum by flow cytometry and colorimetric methods. Expression of heme oxygenase-1 was assessed by RT-PCR. Parallel serial analysis of human stored, washed and rejuvenated RBC packs was conducted to co-relate with porcine data. Data was analysed using and t-tests. The data are reported as mean ± SE. Results: Removing inflammatory MP by washing suppressed leucocyte adhesion in lung but increased serum free haemoglobin and serum/pulmonary iron levels (see Table 1 ). That in turn activated endothelium through a non-standard pathway, which lead to higher in-vivo pulmonary vascular resistance index and reduced renal vasodilation (see table ). Rejuvenation eliminated generation of free haemoglobin and iron, prevented endothelial dysfunction and functional and histopathological features of TRALI. Conclusions: We identified two components of stored blood transfusion that contribute to organ injury. MP activate leukocytes and are removed by RBC washing. Free iron and haemoglobin is generated during washing and is eliminated by Rejuvenation.